Quartz sand use in hydraulic and sanitary engineering - Kuzmanić, Tamara (Acta hydrotechnica, 2020)
An overview of the production and usage of quartz sand as a special sort of sand for civil engineering is presented from the formation of sand deposits, through mining and processing methods, to its final use, with an emphasis on its use in civil engineering, i.e. in water filtration. Quartz is found in sedimentary, metamorphic, and igneous rocks. During sand formation in the fluvial environment, quartz grains are highly resistant to weathering and mechanical wear, and can be transported a long way without changes to size and form. Therefore, quartz is the main constituent of most natural sands. Quartz and quartz sand are ubiquitous raw materials used in a wide range of products in civil engineering due to their chemical inertia and high temperature resistance. An example of a quartz sand deposit and processing plant in Slovenia is presented as a practical case study on quartz sand application. The described applications using quartz sand are the best available technologies in sanitary and hydraulic engineering to be used for a move towards a circular economy, smart houses, and smart cities.
Keywords: čiščenje vode; filter media; filtrirni mediji; granular media; granulometry; green infrastucture; kremenov pesek; peščeni filter; quartz sand; sand filter; water treatment; zelena infrastruktura; zrnati mediji; zrnavostna sestava